Tanggung Jawab Direksi Terhadap Keputusan Investasi dan Pengelolaan Keuangan Berbasis Artificial Intelligence dalam Perseroan Terbatas di Indonesia - Fransisko Pasaribu; Roida Nababan; Samuel Situmorang (Jurnal Ilmu Hukum, 2026)
The use of Artificial Intelligence in investment decision-making and corporate financial management constitutes part of the digital transformation in corporate governance, which requires legal certainty regarding the liability of the Board of Directors. While the use of AI has the potential to enhance efficiency and accuracy in business analysis, it simultaneously gives rise to legal risks where decisions generated by AI result in losses to the company.This study aims to analyze directors’ legal liability for corporate financial losses arising from the use of Artificial Intelligence in investment decisions and to examine the application of the Business Judgment Rule and fiduciary duty as forms of legal protection. This research employs normative legal methods using statutory and conceptual approaches, relying on primary, secondary, and tertiary legal materials. The findings indicate that AI does not constitute a legal subject; therefore, liability remains with directors as final decision-makers. The use of AI expands the directors’ duty of care by requiring technological risk awareness and system oversight. Legal protection under the Business Judgment Rule applies when decisions are made rationally, based on adequate information, and free from conflicts of interest. Excessive reliance on AI without critical evaluation may be considered negligence. Accordingly, AI utilization in corporations necessitates stronger fiduciary duty standards and good corporate governance.